The Dynamics of School and Work in Rural Bangladesh - Ridao-Cano, Cristóbal (World Bank, Washington, D.C., 2013)
Canals-Cerdá and Ridao-Cano investigate the effect of work on the school progress of rural Bangladeshi children. They specify a dynamic switching model for the sequence of school and work outcomes up to the end of secondary school, where the switching in each school level is determined by the endogenous work history of the child up to that level. This approach allows the authors to evaluate the dynamic effects of work on school progress. They find that work has a negative and sizable effect on school progress and are able to measure this effect for different groups of children. Their results highlight the relevance of policies aimed at increasing school progress through reductions in child work and the importance of accompanying these policies by efforts to improve the adverse environment that working children face. The authors evaluate the dynamic effects of three policies: compulsory primary schooling, compulsory school entry at age six, and universal access to secondary school. They find that these policies have a sizable effect on school progress and child labor.